The Effect of Recruitment, Placement and Motivation on Employee Performance at PDAM Tirta Jeneberang, Gowa Regency - Iqwani Khaeratulnisa; Muhammad Rusydi; Agussalim Harrang (Eduvest - Journal of Universal Studies, 2025)
This study aims to find out and analyze the Influence of Recruitment on Employee Performance, Placement on Employee Performance, and Motivation on Employee Performance at PDAM Tirta Jeneberang, Gowa Regency. This type of research is a quantitative research with a sample of 43 respondents using a questionnaire as data collection. The analysis used is Multiple Linear Regression Analysis using the SPSS Version 24 application. The results of the study show that: 1. Recruitment has a positive and significant effect on employee performance, 2. Placement has a positive and significant effect on employee performance, and 3. Motivation has a positive and significant effect on employee performance.